The endowment effect on entrepreneurs: A risky attachment - Echeverry Peñón, Isabela; Reyes Ortega, Santiago (Estudios de Economía, 2018)
This paper presents evidence on the role of the endowment effect in shaping the risk-taking behavior of entrepreneurs, and how the potential of losing their firms lead them to take higher risks. This study uses an experimental design with 466 entrepreneurs in Cali, Colombia. Results show that entrepreneurs are more likely to accept riskier bets when those are related to the possession of their companies than in non-framed lotteries. The data shows that the existence of the endowment effect increases the certainty equivalent of a lottery, for the median entrepreneur, by 36.5%. This could explain why many entrepreneurs prefer to continue operating their underperforming firms, as well as why many entrepreneurs overvalue their firms during investment processes. This paper presents an alternate view on the drivers behind entrepreneurs’ risk-taking behavior and opens a door for future research on the role of biases on entrepreneurs’ decision-making processes.